Discrimination and Daycare Choice: Evidence from a Randomized Survey - Mongoljin Batsaikhan; Mette Gørtz; John Kennes; Ran Sun Lyng; Daniel Monte; Norovsambuu Tumennasan (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
We use a randomized survey to study how discrimination affects parenting choices. In our survey, parents with young children choose between two public daycares, which are described by testimonials from other (fictitious) parents. The testifying parents in the first daycare describe a free play institution, which reflects a pro-typical Scandinavian 'permissive parenting' approach to childcare. The testifying parents in the second daycare describe a more structured daycare, which reflects an alternative approach to child care that is broadly consistent with 'paternalistic parenting'. We randomize the fictitious names of the testifying parents across respondents. We find bias against ethnic minorities among parents who prefer a structured child care institution but not among parents who prefer free play one. These biases are not reduced when we provide additional information on testifiers' professions. Our findings offer validation for a model of parenting where biases regarding discrimination are likely to come from parents preferring less permissive/more authoritarian methods of parenting.
Keywords: D15; D63; J15; I24; 330; discrimination; survey experiment; parenting style; daycare choice